Are Reports of Pain, Disability, Quality of Life, Psychological Factors, and Central Sensitization Related to Outcomes of Quantitative Sensory Testing in Patients Suffering From Chronic Whiplash Associated Disorders?. Issue 3 (March 2022) - Lenoir, Dorine; Willaert, Ward; Ickmans, Kelly; Bernaers, Lisa; Nijs, Jo; Malfliet, Anneleen; Danneels, Lieven; Leysen, Laurence; De Pauw, Robby; Cagnie, Barbara; Coppieters, Iris; Meeus, Mira
Abstract : Background: Chronic whiplash associated disorders (CWAD) are characterized by long-lasting symptoms of neck pain occurring after an acceleration-deceleration injury. Central sensitization (CS) has been suggested as the possible underlying mechanism for these symptoms, and is characterized by changes in the central nervous system. Besides CS, psychological factors are believed to play an important role in the experience of (chronic) pain. Objective: Investigating the relationships between self-reported pain, disability, quality of life, psychological factors, and symptoms of CS; and electrical-based quantitative sensory testing (QST) outcomes in CWAD patients. Secondly, to investigate the differences in QST between CWAD patients and pain-free controls. Methods: Seventy-two individuals with CWAD and 55 pain-free controls underwent electrical stimuli-based QST. Detection and pain thresholds (EPT), temporal summation (TS), and conditioned pain modulation were examined. Spearman correlation and linear mixed models analyses were performed to assess, respectively, the hypothesized associations and group differences in QST. Results: The Pain Catastrophizing magnification subscale correlated with the left wrist EPT ( r =−0.332; P =0.004), and the Pain Anxiety Symptom Scale-20 with the left wrist ( r =−0.325; P =0.005) and ankle ( r =−0.330; P =0.005) EPT. TS at the ankle correlated with the CS inventory ( r =0.303; P =0.010), Short Form 36 pain subscale ( r =−0.325; P =0.005), and Illness Perception Questionnaire revised consequences subscale ( r =0.325; P =0.005). EPTs left ( P =0.011) and right wrist ( P =0.023) were lower in the CWAD group, but conditioned pain modulation and TS did not differ between groups. Conclusion: QST outcomes relate to psychological constructs, rather than to self-reported pain intensity and distribution. Local hyperalgesia was found in individuals with CWAD, but no differences in endogenous pain facilitation nor inhibition.